2020
DOI: 10.1021/acs.inorgchem.0c02563
|View full text |Cite
|
Sign up to set email alerts
|

Probing CO Generation through Metal-Assisted Alcohol Dehydrogenation in Metal-2-(arylazo)phenol Complexes Using Isotopic Labeling (Metal = Ru, Ir): Synthesis, Characterization, and Cytotoxicity Studies

Abstract: The reaction of 2-{2-(benzo [1,3]dioxol-5-yl)-diazo}-4-methylphenol (HL) with [Ru(PPh 3 ) 3 Cl 2 ] in ethanol resulted in the carbonylated ruthenium complex [RuL(PPh 3 ) 2 (CO)] (1), wherein metal-assisted decarbonylation via in situ ethanol dehydrogenation is observed. When the reaction was performed in acetonitrile, however, the complex [RuL(PPh 3 ) 2 (CH 3 CN)] (2) was obtained as the main product, probably by trapping of a common intermediate through coordination of CH 3 CN to the Ru(II) center. The analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 102 publications
0
20
0
Order By: Relevance
“…From this graph it is evident that an increase in hydrophobicity correlates with a steady increase in cytotoxicity for all three cell lines. These results suggest that hydrophobic character, a property that eases the ability to cross the cellular membrane, leading to better availability of compounds in its target, may be useful to the maximum cellular uptake of oxidovanadium complexes and the associated cytotoxic effects. The reasons for the complex ability for cell permeation through the lipid layer of the cell membrane may be attributed to the coordination behavior, the polarity of the ligand, and the reduced central metal ion through charge equilibration. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…From this graph it is evident that an increase in hydrophobicity correlates with a steady increase in cytotoxicity for all three cell lines. These results suggest that hydrophobic character, a property that eases the ability to cross the cellular membrane, leading to better availability of compounds in its target, may be useful to the maximum cellular uptake of oxidovanadium complexes and the associated cytotoxic effects. The reasons for the complex ability for cell permeation through the lipid layer of the cell membrane may be attributed to the coordination behavior, the polarity of the ligand, and the reduced central metal ion through charge equilibration. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…The results were expressed as percentages of the control. % cell viability = [mean OD of the treated cell/mean OD of the control] × 100 IC 50 value of the compounds was calculated from the absorbance concentration plot following standard procedure [51,66].…”
Section: Cytotoxicity Analysis Through Mtt Assaymentioning
confidence: 99%
“…In order to determine the cytotoxic effect of the Mo complexes, MTT cell viability assay was carried out. ,,, In the present investigation, the complexes with a different number of metal centers and substituents in their ligand backbone were tested for their toxicity on three different cell lines: human cervical cancer (HeLa), human colon cancer (HT-29), and noncancerous mouse embryonic fibroblast (NIH-3T3) cell lines.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In continuation of our research on the pharmacological properties of various transition metal complexes, ,, herein the synthesis of two monomeric, [MoO 2 (L 1 )­(MeOH)] ( 1 ) and [MoO 2 (L 2 )­(EtOH)] ( 2 ), and two mixed-ligand dimeric, [{MoO 2 (L 1–2 )} 2 (μ-4,4′-bipy)] ( 3 and 4 ), dioxidomolybdenum­(VI) complexes from two aroylhydrazone ligands (H 2 L 1–2 ) is reported. The complexes revealed a distorted octahedral geometry with the sixth labile coordination site occupied by the solvent molecule (MeOH/EtOH) in case of the monomeric complexes and the coligand 4,4′-bipyridine in case of the dimeric complexes. Hydrazones are important set of ligands, as they manifests a vast range of pharmaceutical activities. It has been demonstrated that their biological properties are considerably enhanced upon complexation to metal ions .…”
Section: Introductionmentioning
confidence: 99%